Dyspnea, Tachycardia, and New Onset Seizure as a Presentation of Wilms Tumor: A Case Report. (5th February 2014) - Li, Linda; Light, Jennifer; Marchick, Michael; Hoelle, Robyn
Abstract : Wilms tumor is found in 1 in 10, 000 children and most commonly presents in asymptomatic toddlers whose care givers notice a nontender abdominal mass in the right upper quadrant. This case of Wilms tumor presented as a critically ill eleven-year old with significant tachypnea, dyspnea, vague abdominal pain, intermittent emesis, new onset seizure, metabolic acidosis, and hypoxemia. This is the first case in the literature of Wilms Tumor with cavoatrial involvement and seizure and pulmonary embolism resulting in aggressive resuscitation and treatment. Treatment included anticoagulation, chemotherapy, nephrectomy, and surgical resection of thrombi, followed by adjunctive chemotherapy with pulmonary radiation.